Windows XP for Power Users: Power Pack - Simmons, Curt (Wiley Publishing, 2011)
Shows power users how to take Windows XP to the next level, focusing on functionality, networking, and overall performance Features to-the-point coverage that skips introductory explanations and focuses instead on the real-world tips and tricks power users need to become more productive Written in a friendly, approachable style by experienced XP author and power user Curt Simmons Topics covered include scripting, managing applications, making the most of digital media, power management, hardware management, the registry and file systems, security, auditing, backup and data storage, system performance, system recovery, Microsoft's popular download XP Power Toys, networking, and wireless